Proposed Marketing Strategy of Ina Cookies Surabaya (The Indonesian Journal of Business Administration, 2021)
Ina Cookies founded by Hj.Rr. Ina Wiyandini since 1998. Ina Cookies opened distributors in Surabaya has been around for 5 years ago. After 5 years, sales performance continued to increase. But in 2020 the business world experienced a storm due to covid 19, so sales performance decreased drastically, especially sales made by traditional marketing channels, namely marketers and outlets in modern shopping centers. The study aims to explore the issue of declining sales by conducting external analysis of PEST Analysis, customer Analysis and competitor analysis, combining internal analysis of business of Segmentation, targeting, positioning, and marketing mix. Referred to business analysis, resulted what is root causes of business issues. Using TOWS Matrix analysis was resulted the choice of alternative strategies and find the right marketing strategy to solve business problems.The business solution was choosing program Ina Cookies for Giving where Ina Cookies Surabaya switch target market from product to services. Ina Cookies provides a solution for those not only who want to consume cookies but also for customers who want to give Ina Cookies as a gift. To realize that, Ina Cookies Surabaya develop product support services in the form of cookies parcel packaging.Keywords: Ina Cookies, Cookies, marketing channel.